2022
DOI: 10.3390/ma15062183
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Materials for Orbital Wall Reconstruction—An Overview

Abstract: The reconstruction of an orbit after complex craniofacial fractures can be extremely demanding. For satisfactory functional and aesthetic results, it is necessary to restore the orbital walls and the craniofacial skeleton using various types of materials. The reconstruction materials can be divided into autografts (bone or cartilage tissue) or allografts (metals, ceramics, or plastic materials, and combinations of these materials). Over time, different types of materials have been used, considering characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 90 publications
(124 reference statements)
0
24
0
Order By: Relevance
“…A wide range of materials can be used for 3D printing, including metals, hydrogels, etc. However, the most stable 3D printing material available at present is polycaprolactone [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of materials can be used for 3D printing, including metals, hydrogels, etc. However, the most stable 3D printing material available at present is polycaprolactone [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 Along with the rapid development of tissue engineering, bioresorbable materials have become a hotspot and have been applied widely in clinic. 4 A 10-year retrospective study demonstrated the safety and effectiveness of bioresorbable materials in orbital fracture surgical repair. 10 Seen et al 11 also proved that bioresorbable materials have comparative safety and effectiveness in isolated BOF.…”
Section: Discussionmentioning
confidence: 99%
“…Other advantages to custom 3D-printed implants are shortened intraoperative times, reduced length of anesthesia, and greater precision in restoration of orbital volume to match the unaffected orbit. 9 In addition, the revision rates of orbital reconstruction using 3D-printed models and PSI were lower compared with reconstruction with standard implants. 20 One of the challenges to using PSIs has been cost.…”
Section: Advantages Of Psismentioning
confidence: 97%
“…Several alloplastic materials are available for reconstructing simple, single wall defects, such as Medpor (Stryker, MI), polytetrafluoroethylene (PTFE), silicone, preshaped titanium plates (Synthes/DePuySynthes, KLS Martin, Stryker), titanium mesh, and resorbable materials such as polydioxanone sulfate membrane (Ethicon, Norderstedt, Germany). 8,9 Bone grafts were used in the past but have been associated with unpredictable resorption rates and increased donor site morbidity, thus limiting their current use in favor of alloplastic material. 10,11 Medpor is a nonresorbable, porous polyethylene implant that is easy to shape and has had similar results as bone tissue with fewer infection rates.…”
Section: Types Of Orbital Implantsmentioning
confidence: 99%
See 1 more Smart Citation